"Not Gonna Hold Me Back": Coping and Resilience in Students with Disabilities. Issue 2 (15th March 2019) - Vaccaro, Annemarie; Moore, Adam; Kimball, Ezekiel; Troiano, Peter F.; Newman, Barbara M.
Abstract : A constructivist grounded theory study with 59 students with diverse disabilities from four different universities offers insight into coping strategies and long-term resilience for this rapidly growing, but marginalized, population. Embracing a strengths perspective, we present narratives from student exemplars who used creative coping strategies, drew upon past successes to develop successful coping patterns, and exuded resilience as they navigated challenging postsecondary learning environments. Findings reinforce the importance of person-centered student affairs practice.